Peramalan Penjualan dengan Metode Exponential Smoothing (Studi Kasus : Penjualan Bakso Kemasaan/Kiloan Rumah Bakso Bang Ipul) - Hisyam Ihsan; Syam, Rahmat; Fahrul Ahmad (Journal of Mathematics, Computations and Statistics, 2018)
Sales forecasting enables an optimal policy of the company had to make the appropriate decisionand maintain the efficiency of operational activities. Rumah Bakso Bang Ipul is a business that sellspackaged meatballs. Therefore, Rumah Bakso Bang Ipul is in need of sales forecasting to increase profitand avoid the occurrence or lack of supply of packaged meatballs. This research was conducted by themethod of exponential smoothing forecasting. As for parameter or a used predicting sales is a =0.1,0.2,0.3,0.4,0.5,0.6,0.7,0.8, and 0.9. single exponential smoothing do a comparison in determining thevalue of a, by searching for the value of such a trial and error to find a that has minimum error with searchmethod using the mean absolute error (MAE) and mean squared error (MSE). So that selected a = 0.1 withMAE value = 6.23 and MSE Value = 58.32. Based on these results, using the method of single exponentialsmoothing and retrieved results forecasting Rumah Bakso Bang Ipul in July 2018 as much as 48 kilograms.